Innovation in The Marketing Mix of Educational Services in Increasing Competitiveness - Sahri, Sahri; Mutohar, Prim Masrokan; Sujianto, Agus Eko (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
This study aims to examine the innovation of the marketing mix of educational services in increasing competitiveness and customer value at SMP Ar Rahmat. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observation, and documentation. The results showed that SMP Ar Rahmat has innovated the marketing mix in several aspects, such as product innovation, price, promotion, and place. The innovation is directed to provide added value for customers and increase student and parent satisfaction. This research provides advice for SMP Ar Rahmat in innovating the marketing mix, such as improving service quality, expanding the reach of promotions, offering more varied educational programs, providing financial assistance, and collaborating with educational institutions or companies. This research can provide input for decision makers in the world of education to innovate the marketing mix as an effort to increase competitiveness and customer value in schools.